Zygoptera systematics: past, present, and future - Sutherland, Laura N. (2025)
Odonata is a midsized insect order (~6420 species) containing 3 suborders: Anisoptera (dragonflies, 3,120 species), Zygoptera (damselflies, ~3,297 species), and the intermediate Anisozygoptera (~3 species). In this review of the suborder Zygoptera, we provide a brief overview of their biology, ecology, and natural history. We also review the current state of their systematics and phylogenetics, highlighting remaining higher-level classification (eg family, superfamily) issues to address. Lastly, we will emphasize areas that are still in need of exploration which would greatly improve our nderstanding of the group.